(untitled) (Journal of Engineering, 2022)
Self-repairing technology based on micro-capsules is an efficient solution for repairing cracked cementitious composites. Self-repairing based on microcapsules begins with the occurrence of cracks and develops by releasing self-repairing factors in the cracks located in concrete. Based on previous comprehensive studies, this paper provides an overview of various repairing factors and investigative methodologies. There has recently been a lack of consensus on the most efficient criteria for assessing self-repairing based on microcapsules and the smart solutions for improving capsule survival ratios during mixing. The most commonly utilized self-repairing efficiency assessment indicators are mechanical resistance and durability. On the other hand, Nondestructive methods have been widely used to visualize and assess cementitious composites, self-repairing behavior. However, certain issues remain, such as crack spread behavior, repairing agent kinetics on discrete crack surfaces, and the influence of inserted capsules on the mechanical characteristics of self-repaired cementitious composites, all of which require more investigations.